DG sizing and DNR based on REPSO for power losses reduction - Sulaima, Mohamad Fani; Napis, Nur Faziera; Nor, Mohd Khanapiah; Mohd Dahalan, Wardiah; Mokhlis, Hazlie (2014)
The detrimental of losses in network can be solved by using Distribution Network Reconfiguration (DNR) and sizing the Distribution Generation (DG) concurrently. In determining the optimal sizing of DG and identifying the switching operation plan for network reconfiguration, an optimization method which is called as Rank Evolutionary Particle Swarm (REPSO) will be introduced. The main objectives of this paper are to minimize the total power losses in a radial distribution network and to find the most accurate and acceptable size of DG. A comprehensive performance analysis will be carried out on IEEE-33 bus system to show the effectiveness of the REPSO over conventional PSO and hybridization EPSO method. The reliability of proposed method will hope to help the power system engineer in reducing the distribution feeder losses and improve system security in the future.